UPAYA KEJAKSAAN DALAM MELAKUKAN PENYIDIKAN DAN PENYITAAN TERHADAP HARTA HASIL KEJAHATAN PENCUCIAN UANG PADA TINDAK PIDANA KORUPSI - Nilma Lubis; Marlina Marlina; Ibnu Affan (LPPM YPITI, 2021)
The investigation of assets in the crime of money laundering which is the result of a criminal act of corruption by the prosecutor's investigator generally refers to and is guided by the Criminal Procedure Code. The obstacle for the prosecutor's investigator to carry out investigations and confiscation of assets in connection with the crime of money laundering is the difficulty in revealing the whereabouts of the assets owned by the suspect, due to the efforts made by the suspect to hide his assets. The prosecutor's investigator's efforts to carry out investigations and confiscation of assets resulting from corruption related to the criminal act of laundering, namely optimizing the investigation of the assets of corruption suspects. When the suspect's assets are found, then the investigators can confiscate the assets.